Social scientific research - Brancati, Dawn (Los Angeles : London : Sage Publications, 2018)
Offering an engaging and entertaining introduction to research methods, this is a practical and easy-to-use companion for all new researchers and students in the social sciences. Covering all the key stages of the research process, this book guides students in navigating some of the biggest challenges in developing a research project -- Publisher's description.
What is social science research? -- Research ethics -- Identifying a research question -- Conducting a literature review -- Building effective concepts -- Making strong arguments -- Method selection -- Mixed methods research -- Case selection -- Interviews -- Focus groups -- Participant observation -- Process tracing -- Comparative case method -- Quantitative measures -- Quantitative data -- Content analysis -- Surveys -- Experiments -- Observational studies -- Social scientific writing.
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Human behavior -- Research